A luta do Bispo Dom José de Medeiros Delgado por educação escolar para todos (Caicó-RN, 1941-1951) - Brito, Paula Sônia de (2004)
The socioeducational program of actions developed by Dom José de Medeiros Delgado, first Bishop of Diocese of Caicó city in Rio Grande do Norte, from 1941 to 1951, is analyzed by the present work in a historical perspective, based upon the school culture refecence.Through this reference point, the general and peculiar school culture proper of catholic schools founded by Dom Delgado was learned.The schools are: the Ginásio Diocesano Seridoense (1942), the Escola Doméstica Popular Darci Vargas (1943, the Prevocacional School of Caicó (1944) and the Santo Cura d ars Seminar (1946). The socioeducational actions of Dom Delgado Bishop affected seven other towns surrounding Caicó. Places where catholic schools were founded and named after Escola do Pobre . In fight for schools for all social segments of city and rural natures, Dom Delgado founded four rural schools in the surroundings of Serra Negra, São João do Sabugi, Jardim do Seridó e Lagoa Nova. It is also part of his beneficial work the creation of rural cooperatives for the parents of the students from such schools